VLBI wideband digital SSB converter based on poly-phase filter banks - Chen, Lan; Unbehauen, Rolf; Luo, Jintao; Zhang, Xiuzhong; Roßmanith, Hans; Feng, Zhibiao (Electrical Engineering, 2010)
With the further development in astronomy and deep space exploration, the incremental improvements to be expected in the very long baseline interferometry (VLBI) is real-time, high sensitivity, high reliability and wider frequency coverage. The VLBI data acquisition backend plays an important role in the VLBI station. Recently, based on advances in digital hardware like analog-to-digital conversion, digital signal processing, field programmable gate arrays (FPGA) and so on, it has become practical to sample and digitally process the intermediate frequency signal directly. Digital base-band converters (DBBC) will replace analog base-band converters (ABBC) in the VLBI data acquisition backend. This paper presents a sequence of simple modifications to sampled data structures based on the analog prototype system to obtain the basic poly-phase structure in a VLBI data acquisition backend. The theoretical principles of a digital SSB down converter are discussed in detail. The approach adopts multi-rate signal processing for the designed filters in a digital SSB down converter which is carried out by virtex-4 FPGA chips. The observation result shows this model of DBBC is of better performances than ABBC.
Keywords: VLBI; Data acquisition back end; Digital base-band converter; SSB; FFT; Poly-phase filter banks